Hanakam & Schuller - Trickster - Hanakam, Markus 1979-; Schuller, Roswitha 1984- (De Gruyter, 2016)
Hanakam & Schuller are tricksters. As artists and researchers, they remodel the rules of fine art, creating idiosyncratic orders and new world designs incorporated in videos and objects. The artefacts of the two artists from Vienna are "Gestalt-changers"; they change their outer shape and re-appear in a number of different contexts. The trickster art book illustrates the oeuvre and provides an insight into its making using multi-page photo spreads from video stills, and production photographs. The Arkadikon essay captures readers and leads them to contemporary hypothetical landscapes, deconstructing them as modern surrogates of an increasingly virtual world. The artists discuss ideal, pop, aura and abduction with Angela Stief, Anselm Franke, Uta Grosenick, Annette Hünnekens, Wolfgang Ullrich, Lois Weinberger, Stephanie Weber und Oliver Zybok
Keywords: Hanakam, Markus -- 1979-; Schuller, Roswitha -- 1984-; Artefakt; Hanakam & Schuller; Künstlerbuch; Rollenspiel; Videokunst; Objektkunst; Bildband